Decay of Trichomes of Arthrospira platensis After Permeabilization Through Pulsed Electric Fields (PEFs) Causes the Release of Phycocyanin - Knappert, Justus; Nolte, Jonas; Friese, Natalya; Yang, Ye; Lindenberger, Christoph; Rauh, Cornelia; McHardy, Christopher (Frontiers in Sustainable Food Systems, 2022)
The cyanobacterium Arthrospira platensis is a promising source of edible proteins and other highly valuable substances such as the blue pigment-protein complex phycocyanin. Pulsed electric field (PEF) technology has recently been studied as a way of permeabilizing the cell membrane, thereby enhancing the mass transfer of water-soluble cell metabolites. Unfortunately, the question of the release mechanism is not sufficiently clarified in published literature. In this study, the degree of cell permeabilization (cell disintegration index) was directly measured by means of a new method using fluorescent dye propidium iodide (PI). The method allows for conclusions to be drawn about the effects of treatment time, electric field strength, and treatment temperature. Using a self-developed algorithm for image segmentation, disintegration of trichomes was observed over a period of 3 h. This revealed a direct correlation between cell disintegration index and decay of trichomes. This decay, in turn, could be brought into a direct temporal relationship with the release of phycocyanin. For the first time, this study reveals the relationship between permeabilization and the kinetics of particle decay and phycocyanin extraction, thus contributing to a deeper understanding of the release of cell metabolites in response to PEF. The results will facilitate the design of downstream processes to produce sustainable products from Arthrospira platensis.